pembelajaran berbasis proyek pada siswa efl dalam menulis esai - Amatul Firdausah; Dina Merris Maya Sari (Jurnal Ilmiah Wahana Pendidikan, 2020)
Essay writing with Project Based Learning on EFL students 'is considered as one of the most important academic courses in a supposed program help develop students' ability. The subjects of this study were 10 class 2019 A students of STKIP PGRI Sidoarjo English language education study program. The instrument used by the researcher was a questionnaire, observation checklist and a rubric score. The data analysis technique uses qualitative data. In analyzing essays writing data using 15 quistionnaires about the project-based application method (PBL) in writing essays using google form accompanied by the answer "yes" or "no". Respondents who answered 'yes' were 74% and those who answered 'no' were 26%. In the observation checklist that observes lecturer and student activities from beginning to end of essay writing learning. In collecting the rubric score data by assessing the results of writing essays. Based on these data we can know from that project-based learning (PBL) can be applied well and is suitable for teaching essay writing to EFL students. Students also gave a positive response to this method. The aim is to describe the application of project-based learning (PBL) methods to EFL students and to describe the writing of essays by EFL students when learning using project-based learning (PBL) methods for EFL student